A Rare Malignant Paradox In The Oesophagus: Case Report Of Carcinosarcoma With Pathological Insights - M, Priyanka; Amitkumar, Kalaivani; E, Ashwini (Journal of Neonatal Surgery, 2025)
Oesophageal carcinosarcoma is a rare biphasic malignant tumour composed of both epithelial and mesenchymal components. A 64-year-old Indian woman presented with progressive dysphagia, weight loss, and decreased appetite for six months. Imaging revealed a well-defined, homogeneously enhancing submucosal lesion along the posterior oesophageal wall, suggestive of a benign lesion such as leiomyoma. Upper gastrointestinal endoscopy identified a large submucosal mass with surface ulceration. biopsy from the ulcer showed atypical pleomorphic cells suggestive of carcinoma. The patient underwent video-assisted thoracoscopic hybrid McKeown esophagectomy with two-field lymphadenectomy. Gross examination revealed a 5 x 3 x 3 cm polypoid mass confined to the submucosa. Histopathological evaluation demonstrated a biphasic tumour with solid nests of squamous epithelial cells showing comedo-type necrosis and a pleomorphic spindle cell component. Immunohistochemistry confirmed the diagnosis of carcinosarcoma, with strong cytokeratin and p63 positivity in the epithelial component and strong vimentin positivity in the mesenchymal component. The tumour was staged as pT1b N0 Mx, with all margins free of tumour and uninvolved lymph nodes. This case highlights the need for thorough histological and immunohistochemical assessment of oesophageal submucosal lesions, even when radiological features suggest a benign process. Early surgical management combined with adjuvant chemotherapy may improve outcomes in such rare and aggressive tumours.